An acoustic-articulatory study of bilingual vowel production: Advanced tongue root vowels in Twi and tense/lax vowels in Ghanaian English. (May 2017) - Kirkham, Sam; Nance, Claire
Highlights: We compare the Twi [ATR] and Ghanaian English [TENSE] contrasts in bilinguals. We also report data from British English speakers producing the [TENSE] contrast. We analyse acoustic and articulatory (ultrasound tongue imaging) data. Bilingual speakers produce contrasts in similar ways, but with language-specific differences. Bilinguals have different articulatory goals for similar cross-linguistic contrasts. Abstract: This article investigates the acoustic and articulatory correlates of vowel contrasts in bilingual speakers. We analyse data from bilingual speakers of Twi (Akan) and Ghanaian English, with the aim of examining how the production of the advanced tongue root vowel contrast in Twi relates to the production of the tense/lax vowel contrast in Ghanaian English. These data are compared to tense/lax vowel data from monolingual British English speakers. The acoustic results show that Twi and Ghanaian English mainly rely on F1 for distinguishing [ATR] and [TENSE] vowels, whereas British English uses F1, F2, F3 and duration for the [TENSE] contrast. The ultrasound tongue imaging data show tongue root distinctions across all languages, while there are consistent tongue height distinctions in British English, no height distinctions in Ghanaian English, and small height distinctions for some vowels in Twi. Twi has the weakest correlation between F1 and tongue root advancement, which suggests that the [ATR] contrast may involve additional strategies for pharyngeal cavity expansion that are not present in [TENSE] vowels. In doing so, we show that bilinguals produce similar contrasts in similar ways across their two languages, but that language-specific differences also persist, which may reflect different articulatory goals in each language.